IN VIVO AND IN VITRO APPROACHES TO STUDY ALZHEIMER’S DISEASE: Pharmaceutical Science-Biotechnology - BIPASHA BARUA; SURESH KUMAR (International Journal of Life Science and Pharma Research, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder mainly causes cognitive impairments like deterioration in learning, reading, memory and cognition. The pathological hallmark associated with AD is the accumulation of amyloid beta (Aβ) peptides in the brain of the patients. The Aβ aggregation leads to plaque formation which is the main cause of neurodegeneration. The other characteristic which leads to AD involves cholinergic deficits and synaptic loss. In this review, the various in vivo and in vitro approaches are discussed to understand the pathophysiology of AD.